Object oriented development: integrating analysis, design and implementation - Sandvad, Elmer (DAIMI Report Series, 1990)
Object-orientation is discussed in relation to the traditional division of system development activities: analysis, design and implementation. Object-orientation integrates analysis, design and implementation. This statement is illustrated by introducing an object-oriented graphical notation for analysis as well as design and by showing how this notation can be mapped into the object-oriented programming language BETA. This mapping can be automated. It is shown how the programming environment, the Mjølner BETA System can support integration of the object-oriented notation and BETA, and thereby providing an object-oriented CASE tool that, at least partially, closes the CASE gap between design and implementation.